Severe Plastic Deformation on Powder Metallurgy Cu–Al–Ni Shape Memory Alloys. (2015) - López, G.A.; López-Ferreño, I.; Kilmametov, A.R.; Breczewski, T.; Straumal, B.B.; Baretzky, B.; Nó, M.L.; Juan, J. San
Abstract: High-pressure torsion has been successfully applied to polycrystalline Cu–Al–Ni shape memory alloys that had been prepared by a powder metallurgy methodology. The samples before and after high-pressure torsion were characterized by optical and electron microscopy and differential scanning calorimetry. After high-pressure torsion the alloys became ultra-fine grained and the present phases were identified.